2023
DOI: 10.1002/eqe.3818
|View full text |Cite
|
Sign up to set email alerts
|

Performance recovery of a repaired 4‐storey reinforced concrete structure subjected to shake‐table testing

Abstract: Understanding the effects of repair on reinforced concrete (RC) structures is critical to evaluating their performance in future earthquakes. In this research, a system‐level approach is taken by repairing a previously damaged ¼ scale 4‐storey RC structure and subjecting it to a series of dynamic excitations via shake table testing. The repair was undertaken using common construction materials with the primary motivation of restoring original performance. The performance of the repaired structure was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In this direction, a few research studies focused on innovative structural solutions that can be easily and quickly repaired in the aftermath of an earthquake. 56,57 For example, Zhang et al 57 investigated simple repairing techniques (i.e., retightening the bolts of the FDs) for a novel steel rocking CB joint with FDs to restore the initial performance without losing strength and stiffness. However, experimental evidence on suitable structural restoring techniques for structural performance recovery is still limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, a few research studies focused on innovative structural solutions that can be easily and quickly repaired in the aftermath of an earthquake. 56,57 For example, Zhang et al 57 investigated simple repairing techniques (i.e., retightening the bolts of the FDs) for a novel steel rocking CB joint with FDs to restore the initial performance without losing strength and stiffness. However, experimental evidence on suitable structural restoring techniques for structural performance recovery is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, experimental tests are also essential to evaluate and test the repairability of the structure. In this direction, a few research studies focused on innovative structural solutions that can be easily and quickly repaired in the aftermath of an earthquake 56,57 . For example, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a few research studies are currently focusing on repairing methodologies for the structural performance recovery of buildings (e.g., [21]- [22]). For example, Zhang et al [21] demonstrated the efficiency of a simple repairing technique (i.e., re-tightening the bolts of the FDs) applied on a novel steel CB in restoring the initial performance of the structural system without loss of strength and stiffness.…”
Section: Introductionmentioning
confidence: 99%